Digital Media And Teaching Practices : A Study Of Social Media And Educational Portals (Trinity Journal of Management, IT & Media (TJMITM), 2016)
With the advent of digital media & enhancement of the reach of  internet facilities to everyone’s life, digital media is providing us  a whole new platform for enhanced teaching methodologies to  be inculcated in our education system. Educators will now have  an opportunity to amalgamate face-to-face and digital learning  models to advance an engaged, efficient and affordable model  of learning. Digital media technologies and social media websites  also provide a better medium to engage a diverse student  population. Numerous researches in this field also indicate  that active learning through digital devices is much more  beneficial for students. Social media personalizes the students  or learners approach towards the education system now they  are sharing their experiences and ideas through social media  and educational portals like; Facebook, Twitter, StudyPal.co, Bharatstudent.com, NewsWriters.in and many more which  is totally different from the conventional style of teaching.  These emerging technologies are providing a paradigm shift to  conventional educational practices.This includes changes in key teaching and learning dimensions  at the level of interactivity, medium of communication,  constraints on educational process & learning outcomes. It is  very important for the educationist to come up with new methods  of assessment with the unique competencies of the digital media. The objective of this paper will be to provide the content analysis  of different educational portals their methodology towards  students, their acceptance in them and how they are helping  them to grow in their arena.
Keywords: Digital Media Technologies; Social Media; Educational Portals and Education System